ALEJANDRO DE HALES - SUMO TEÓLOGO Y PRINCIPALMENTE FILÓSOFO - EXPOSICIÓN ELABORADA A LOS DOCE LIBROS DE LA METAFÍSICA DE ARISTÓTELES. - Felipe Mendoza, José María (Scintilla)
This text focuses on the whole translation of Alexander of Hales' introduction to the Metaphysic of Aristotle from Latin into Spanish. The few pages included show comprehensive knowledge about all corpus aristotelicum and a specific division about sciences. Such introduction supports the basis of science about ens qua ens showing its dignity and regency on the other sciences.